THE SCIENTIFIC APPORACHES TO THE ESSENCE OF THE MILITARY OFFICIALAS INTEGRITY - Prylipko, M. (Bulletin of Taras Shevchenko National University of Kyiv. Military-special sciences, 2022)
The article is devoted to defining the essence of scientific approaches to the integrity of military officials. The rationale is given that the existence of a large number of evaluation categories in the concept of integrity greatly complicates the implementation of the practical task of assessing the level of integrity of officials. The task of law in such conditions should be to determine the external manifestations of a person's behavior in accordance with the dichotomy "lawful behavior – violation of legal prescriptions". The role of law in establishing the essence and specific criteria of integrity is decisive. The opportunity arises due to the objectification of the requirements for integrity in regulatory legal acts to create a model of the lawful behavior of a serviceman and fix those deviations from it that are manifestations of non-virtuous behavior. The article determines that these manifestations may or may not form the composition of independent torts, the responsibility for which is provided for by the norms of criminal law, as well as legislation on administrative and disciplinary offenses. The article found that the ability to implement the principles of integrity largely depends on at what stage of military service the corresponding activity begins. Therefore, in order to develop well-established skills of respectable behavior of military personnel in the system of military education, various forms of classes should be more actively introduced, the purpose of which is to understand the moral standards of the profession. The conclusion is drawn that at present several scientific approaches to the essence of the concept of "integrity" have been formed, which were developed by representatives of philosophical, pedagogical, psychological and legal sciences. Depending on the methodology of each field of scientific knowledge, attention is paid to individual aspects of integrity, which can be investigated by the instrumental methods of each science. Of these approaches, legal science plays a decisive role, which is due to the following. Firstly, in law there is the possibility of normative and legal consolidation of the obligatory observance of the requirements of integrity at the level of special acts – codes of professional ethics, which are of a complex moral and legal nature. Secondly, it is in law that there is a model of lawful behavior, a deviation from which constitutes a violation of the requirements for the integrity of a military official. Thirdly, it is the law that governs the legal responsibility of officials, which makes it possible to impose sanctions for specific violations of the requirements of integrity. And, fourthly, the principle of legal certainty inherent in jurisprudence makes it possible to maintain a sufficient degree of objectivity to determine the boundaries of the virtuous behavior of military officials.
Keywords: integrity, military officials, good behavior, codes of professional ethics, responsibility, legal science, prevention of corruption